Subgenome Dominance in an Interspecific Hybrid, Synthetic Allopolyploid, and a 140-Year-Old Naturally Established Neo-Allopolyploid Monkeyflower. Issue 9 (16th August 2017) - Edger, Patrick P.; Smith, Ronald; McKain, Michael R.; Cooley, Arielle M.; Vallejo-Marin, Mario; Yuan, Yaowu; Bewick, Adam J.; Ji, Lexiang; Platts, Adrian E.; Bowman, Megan J.; Childs, Kevin L.; Washburn, Jacob D.; et al.
Abstract : Subgenome differences in levels of transposon methylation mirror increases in subgenome-specific expression bias observed over generations following hybridization and allopolyploidization in Mimulus . Abstract: Recent studies have shown that one of the parental subgenomes in ancient polyploids is generally more dominant, having retained more genes and being more highly expressed, a phenomenon termed subgenome dominance. The genomic features that determine how quickly and which subgenome dominates within a newly formed polyploid remain poorly understood. To investigate the rate of emergence of subgenome dominance, we examined gene expression, gene methylation, and transposable element (TE ) methylation in a natural, <140-year-old allopolyploid ( Mimulus peregrinus ), a resynthesized interspecies triploid hybrid ( M. robertsii ), a resynthesized allopolyploid ( M. peregrinus ), and progenitor species ( M. guttatus and M. luteus ). We show that subgenome expression dominance occurs instantly following the hybridization of divergent genomes and significantly increases over generations. Additionally, CHH methylation levels are reduced in regions near genes and within TEs in the first-generation hybrid, intermediate in the resynthesized allopolyploid, and are repatterned differently between the dominant and recessive subgenomes in the natural allopolyploid. Subgenome differences in levels of TE methylation mirror the increase in expression bias observed over the generations following hybridization. These findings provide important insights into genomic and epigenomic shock that occurs following hybridization and polyploid events and may also contribute to uncovering the mechanistic basis of heterosis and subgenome dominance.